The Dynamic Mechanism of Digitization of County Agriculture in the Qinghai-Tibet Plateau: Analysis of Institutional Approach of Zhuo-Sang Mode in Litang County, Sichuan Province - Zhu Huasheng; Dai Jiaxin (Redai dili, 2023)
Agriculture has been making a new turn toward digitization in developed areas. However, in the underdeveloped ethnic regions of western China, does digitization represent a valuable opportunity or a serious challenge? In this article, Litang County, Sichuan Province, located in the western high plateau region, was taken as an example, and text analysis of multi-source data was performed, including of policy documents, planning texts, website information of agricultural companies and government departments, and materials based on semi-structured interviews with local authorities and leading agricultural companies, with the purpose of discussing the dynamic mechanism of agricultural digitization in underdeveloped western counties. It was found that agricultural digitization in Litang has the following three typical characteristics: 1) full-chain digitization, that is, a closed-loop structure of data is formed through enterprise data centers, local data management platforms, and e-commerce platforms from various links such as vegetable and fruit breeding, planting, condensation logistics, and product sales; 2) multi-agent promotion, that is, agricultural companies, retailers, government departments and their agents, as well as social organizations, cooperate and promote each other in agricultural digital infrastructure construction, data technology application and data management, and agricultural resources integration; 3) coordination within and outside the county, namely timely response to the national rural revitalization strategy, corresponding poverty alleviation policies and local planning goals and action plans, coordination between the matching aid units and local departments and institutions in terms of the dual goals of economic benefits and poverty alleviation, and coordination between agricultural companies, social organizations, platform institutions and farmers, and other stakeholders within and outside the county. This study contributes to the establishment of a four-dimensional analysis framework of natural environment-market-institution-technology based on the institutional analysis of economic geography and enriches the research on economic geography in the field of agricultural digitalization. The main conclusions are as follows. First, the special natural environment in the high plateau area has shaped the constraint conditions and advantages of agricultural development in Litang, which encourages local companies to adopt a differentiation strategy, enter outside segment markets, and create a new evolutionary path using biological and digital technology. Second, the application of digital technology is not only beneficial to meet the needs of remote consumers for production information but also to provide feedback on timely changes in market demand for local agricultural companies, which is conducive to the adjustment and optimization of the decisions of agricultural producers. Technology investment increases production costs, which can be achieved by entering middle- and high-end markets to increase revenue. Third, the digital transformation of leader companies is not only the result of responding to or embedding national and local agricultural digitization strategies, but also puts forward potential requirements for the adjustment and optimization of local institutions and production organizations. Government and leadership companies jointly promote agricultural digitalization. In addition, the national matching poverty alleviation policy enables local governments to obtain scarce resources such as technology, capital, and market opportunities through external support, effectively reducing the risks and costs of digital transformation for leader companies, farmers, and other local production actors and promoting the spatial agglomeration of digital elements and resources through the external economies of the production network. However, it is crucial to take advantage of external support to cultivate local entrepreneurial talent and increase human capital for sustainable local development.